2018
DOI: 10.1128/aac.00517-18
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Multicenter Population Pharmacokinetic Study of Ciprofloxacin in Children with Complicated Urinary Tract Infection

Abstract: Resistance rates for ciprofloxacin, which is labeled for treating complicated urinary tract infections in children, are rapidly rising. As there is limited knowledge on developmental pharmacology of ciprofloxacin, the primary aim of this study was to develop a population pharmacokinetic model for ciprofloxacin in children treated for complicated urinary tract infections. Children to whom ciprofloxacin was prescribed, intravenous (10 to 15 mg/kg body weight every 12 h) or (15 to 20 mg/kg every 12 h), were enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Recently, Meesters et al [11] have developed a population pharmacokinetic model of ciprofloxacin in children with cUTI finding that V d and total plasma CL were 83.6% and 41.5% reduced, respectively, with respect to healthy children and paediatric patients with CF [9,10]. These findings are in accordance with previous observations, indicating that renal impairment affects drug disposition beyond the impact on renal clearance [12].…”
supporting
confidence: 84%
See 2 more Smart Citations
“…Recently, Meesters et al [11] have developed a population pharmacokinetic model of ciprofloxacin in children with cUTI finding that V d and total plasma CL were 83.6% and 41.5% reduced, respectively, with respect to healthy children and paediatric patients with CF [9,10]. These findings are in accordance with previous observations, indicating that renal impairment affects drug disposition beyond the impact on renal clearance [12].…”
supporting
confidence: 84%
“…In the current analysis, the PBPK approach has been used to mechanistically describe the systemic and urinary ciprofloxacin exposure in children suffering from cUTI, a disease causing serious alterations in processes involved in its PK. In fact, a recent pharmacokinetic study of ciprofloxacin administered to cUTI children showed that the apparent V d and the total plasma CL were decreased compared to healthy children (up to a 83.6% and 41.5%, respectively), presenting a degree of inter-individual variability not explained by any of the patient's factors ranging from 60 to 160% [11]. The lack of literature examples extrapolating from healthy subjects to the patient population, thus beyond ontogeny, and towards the population of interest, exemplify the novel contribution of the current work within the extensive literature on both PBPK and ciprofloxacin [9,14,[16][17][18][19][20][21]36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clearance of cipro loxacin is signi icantly lower in new-borns than the other children; however, a wide interindividual variability exists within each age group (Meesters et al, 2018). The postnatal age, current body weight, renal function indicated by serum creatinine concentrations has a signi icant effect on the clearance of cipro loxacin in children.…”
Section: Pharmacokinetics Of Cipro Loxacinmentioning
confidence: 99%
“…The association of renal function and cipro loxacin clearance is explained by the difference in renal physiological and anatomical maturation since cipro loxacin is primarily excreted by the kidneys. Cipro loxacin clearance is increased allometrically with current weight in neonates and young infants and illustrates the independent impact of both gestational and postnatal ages on antenatal and postnatal renal maturation.Fat-free mass and glomerular iltration rate standardized for body surface area may also act as considerable covariates for cipro loxacin clearance in children (Meesters et al, 2018;Payen et al, 2003;Zhao et al, 2014) The clearance of cipro loxacin in children and adults was found to be 29.9 L/hr and 31.9 L/hr with a child to adult ratio of 0.94 whereas V d was found to be 260 and 154L/kg (child: adult-1.69), respectively (Holford et al, 2013). However, more pharmacokinetics studies are required to design an optimum dosage regimen for cipro loxacin in the pediatric population.…”
Section: Pharmacokinetics Of Cipro Loxacinmentioning
confidence: 99%